2019
DOI: 10.22158/rem.v5n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Quality of Governance on Domestic Government Health Spending in West Africa Economic and Monetary Union Countries

Abstract: Government health spending is an important source of sustainable health funding in order to attain the health-related Sustainable Development Goals (SDGs). In low and middle-income countries, domestic government per capita spending on health needed to ensure universal coverage with the most essential health services is estimated at $112 according to Stenberg et al. (2017). In 2015, in West Africa Economic and Monetary Union (WAEMU), average domestic government spending on health per capita was $26 (about one q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The chosen period is limited by the data availability of the ICT and institutional quality indices. Nevertheless, the selected variables are consistent with the literature (Jibir and Aluthge, 2019;Okafor and Eiya, 2011;Azolibe, 2020;Dianda and Ouedraogo, 2021) and economic theory. The primary data source for the analysis is the World Bank's (2022a) World Development Indicators.…”
Section: Data and Empirical Methodology 31 Data And Samplesupporting
confidence: 80%
See 2 more Smart Citations
“…The chosen period is limited by the data availability of the ICT and institutional quality indices. Nevertheless, the selected variables are consistent with the literature (Jibir and Aluthge, 2019;Okafor and Eiya, 2011;Azolibe, 2020;Dianda and Ouedraogo, 2021) and economic theory. The primary data source for the analysis is the World Bank's (2022a) World Development Indicators.…”
Section: Data and Empirical Methodology 31 Data And Samplesupporting
confidence: 80%
“…Simultaneously, in line with a growing literature that investigates the effect of institutional quality on health and education as well as on government spending (Duerrenberger and Warning, 2018; Hsiao et al , 2019; Swaleheen et al , 2018; Saengchai et al , 2020; De Luca et al , 2021; Dianda and Ouedraogo, 2021), the study has revealed that institutional quality has a significant positive effect on the provision of social services in the short and long run for low-income countries. Thus, the second research hypothesis of this study stands to prove that institutional quality has a significant positive effect on institutional quality, which validates the findings of Saengchai et al (2020) based on Asian countries from 1990 to 2018, which showed that civil liberty, regulatory quality and voice and accountability improve the quality of education, as well as Dianda and Ouedraogo (2021) based on WAEMU countries from 2000 to 2015, which showed that institutional quality has positive effects on the accumulation of health capital. Thus, the current study’s findings imply that institutional quality fosters the provision of social services in low-income countries.…”
Section: Discussion and Comparison Of Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Using data from 19 OECD countries, Gerdtham et al (1992) identified the share of public financing to total health expenditure, per capita income, urbanisation as positive and significant determinants of health expenditure. The income elasticity of demand for healthcare being found to be less than unity implying health is a necessary good in the various empirical works (Baltagi & Moscone, 2010; Behera et al, 2020; Dianda & Sirpe, 2020; Font & Novell, 2006; Murthy & Okunade, 2009; Sen, 2005), while another group of scholars claimed health as luxury good, as its responsiveness is sensitive to income change (Gbesemete & Gerdtham, 1992; Hitris & Posnett, 1992; Kiymaz et al, 2006; Newhouse, 1977). Souliotis and Lionis (2005) stated, among the goals of social and economic development, the public health sector will be low priority area if the income elasticity of health expenditure is less than one.…”
Section: Introductionmentioning
confidence: 99%
“…,Dianda and Sirpe (2020),Behera et al (2020),Farag et al (2012),Sen (2005), Chakroun (2010),Gerdtham et al (1998),Baltagi and Moscone (2010), Fernandez et al (2014).…”
mentioning
confidence: 99%